Purification of Saccharomyces cerevisiae eIF4E/eIF4G/Pab1p Complex with Capped mRNA (Journal of Sciences, Islamic Republic of Iran)
Protein synthesis is one of the most complex cellular processes, involving numerous translation components that interact in multiple sequential steps. The most complex stage in protein synthesis is the initiation process. The basal set of factors required for translation initiation has been determined, and biochemical, genetic, and structural studies are now beginning to reveal details of their individual functions in this process. In Saccharomyces cerevisiae, eIF4E is the central component of the eIF4F complex, which binds the 5? cap structure of the mRNA. This complex is significant in many ways. First of all, it is essential for translational initiation, mediating the initial interactions of ribosomes with the mRNA 5? end. Secondly, because of its key role in interacting with the 5? end of the mRNA, and possibly also with proteins such as the poly (A) binding protein (PABP) at the 3? end of the mRNA, the eIF4F complex is thought to be involved in the process of mRNA degradation. Thirdly, eIF4F is a site of translational regulation, responding to signals communicated along the signal transduction pathway that are induced by stress conditions or hormones. To study about the interactions of eIF4E within the eIF4F complex, we tried to find conditions that would enable us to obtain structural data about S. cerevisiae eIF4E/eIF4G/Pab1p interactions. To yield information about the eIF4E/eIF4G/Pab1p complex, affinity chromatography was conducted using synthetic biotinylated capped mRNAs. For this purpose, a capped 55-nucleotide RNA was synthesised and labeled with Biotin-21-UTP at the 3?-end in an in vitro transcription reaction. For Biotin labeling of mRNA, rUTP was substituted with Biotin-21-UTP in the reaction. Soft Link Avidin Resin was used for the isolation of biotinylated mRNA, which can bind eIF4E via the capped structure at the 5?-end of the mRNA and Pab1p via the poly (A) tail at 3? end. These results confirm that a highly pure eIF4E/eIF4G/Pab1p/RNA complex can be generated using the procedures outlined.